Hubungan Antara Kekuatan Otot Ekstremitas Bawah dan Fungsi Kognitif dengan Keseimbangan Tubuh pada Lanjut Usia - Masitha, Siti (Publikasi Indonesia, 2022)
The Elderly is someone who is 60 years old which is characterized by a decrease in lower extremity muscle strength and cognitive function that can affect body balance in the elderly. To determine the relationship between lower extremity muscle strength, cognitive function, and body balance and to determine the dominant factors that affect body balance in the elderly in Gonilan Village. a cross-sectional study involving 94 respondents with a quota sampling technique. Correlation test with the Spearman Rho test, there is no relationship between lower extremity muscle strength and cognitive function with static balance, there is a relationship between lower extremity muscle strength and cognitive function with dynamic balance. There is no relationship between lower extremity muscle strength and cognitive function with static balance. There is a relationship between lower extremity muscle strength and cognitive function with dynamic balance.